A Concise Stereoselective Total Synthesis of (–) - Cephalosporolide D - Umanadh, Yapuri; Omprakash, Gudaparthi; Srinivasareddy, Narahari (Letters in Organic Chemistry, 2015)
A concise stereoselective total synthesis of (-) - Cephalosporolide D, an eight membered lactone ring has been derived from low cost and easily available starting material (±)-propylene epoxide. The key steps involved in this concise synthesis are Sharpless kinetic resolution, Grignard reaction and Yamaguchi macrolactonisation.
Keywords: sharpless kinetic resolution